MAC OS X Lion : the missing manual - Pogue, David, 1963- (Missing manual., 2011)
With Lion, Apple has unleashed the most innovative version of Mac OS X yet--and once again, David Pogue brings his humor and expertise to the #1 bestselling Mac book. Mac OS X 10.7 completely transforms the Mac user interface with multi-touch gestures borrowed from the iPhone and iPad, and includes more 250 brand-new features. This book reveals them all with a wealth of insight and detail--and even does a deep dive into iCloud, Apple's wireless, free syncing service for Macs, PCs, iPhones, and iPads. Perfect for newcomers. Get crystal-clear, jargon-free introduction to the Dock, the Mac OS X fol.